Decolonizing Evaluation: Truth, Power, and the Global Evaluation Knowledge Base - Hur Hassnain (The Evaluation Center at Western Michigan University, 2023)
Evaluations play a critical role in shaping the way international development interventions are designed and managed. This contributes to the fact that there are intrinsic power dynamics at play during the production of evaluation knowledge. In the wake of growing commitments to deal with the repercussions of a colonial past and a prolonged history of white supremacy, there has been growing recognition of the need to decolonize evaluation theory and practice to help foster equality and ensure that evaluation knowledge is generated, shared, and understood universally. Increased efforts are being made to understand the risks involved if evaluations fail to utilize decolonized evaluation methods and approaches. We are faced with questions such as: How can we decolonize evaluation and disrupt unequal power relations? How can the evaluation process itself be transformative and an opportunity for co-liberation? What practical tools and steps facilitate power sharing? How can evaluation be used to advance decolonization and social justice? This paper describes the connection between truth and power and how that relates to the evaluation and decolonization debates. It provides potential starting points for decolonizing evaluation practice, including some examples where this has already been tested. To conclude it focuses on the universalisation of evaluation knowledge and the need to ensure that evaluation knowledge is translated and disseminated via inclusive forms of communication to ensure that learning can be better understood and hence translated into action orientated practice from grassroot to government level.   The aim of this paper is to advance the discussion on decolonizing evaluation practice and provide some potential ways forward in terms of transforming evaluation theory and practice. Keywords Decolonizing evaluation, development, results, learning, accountability